PSMA ligands for PET imaging of prostate cancer - Schwarzenböck, Sarah; Asfhar-Oromieh, Ali (Journal of nuclear medicine, 2017)
Targeting the prostate-specific membrane antigen (PSMA) with 68Ga-labeled and 18F-labeled PET agents has become increasingly important in recent years. Imaging of biochemically recurrent prostate cancer has been established as a widely accepted clinical indication for PSMA ligand PET/CT in many parts of the world because of the results of multiple, primarily retrospective, studies that indicate superior detection efficacy compared with standard-of-care imaging. For high-risk primary prostate cancer, evidence is growing that this modality significantly aids in the detection of otherwise occult nodal and bone metastases. For both clinical indications in recurrent as well as in primary prostate cancer, preliminary data demonstrate a substantial impact on clinical management. Emerging data imply that intraprostatic tumor localization, therapy stratification, and treatment monitoring of advanced disease in specific clinical situations might become future indications. Current criteria for image reporting of PSMA ligand PET are evolving given the expanding body of literature on physiologic and pathologic uptake patterns and pitfalls. This article intends to give an educational overview on the current status of PSMA ligand PET imaging, including imaging procedure and interpretation, clinical indications, diagnostic potential, and impact on treatment planning.